204 A RETROSPECTIVE REVIEW OF THE ANTERIOR AND POSTERIOR APPROACHES TO SUBAXIAL CERVICAL DISLOCATIONS AND FRACTURE SUBLUXATION. (1st January 2006) - Porter, S.; Roberto, R.
Abstract : Purpose of Study: To compare the advantages and disadvantages of anterior and posterior approaches for treatment of subaxial cervical dislocation and fracture subluxation. Methods Used: A retrospective review was performed of all patients undergoing operative treatment for subaxial facet dislocations and fracture subluxation from December 2000 through September 2005. X-rays were measured for preoperative and postoperative kyphosis and anterolisthesis. X-rays were also examined for fusion quality at final follow-up and for loss of reduction or implant failure. Surgical variables were recorded, including EBL and postoperative wound complications. Twenty-six patients were identified meeting inclusion criteria, 8 treated by anterior methods, 18 treated by posterior fusion and plating. Summary of Results: The anterior cervical fixation procedure was noted to be associated with a greater correction of posttraumatic kyphosis with a mean correction of 13 degrees. The mean kyphosis in the anterior group was 8 degrees preoperative, correcting to a mean postoperative value of -5 degrees (p = .003). In the posterior fusion and plating group the mean preoperative value for kyphosis was 7 degrees, correcting to a postoperative mean of 1 degree ( p = .03). There was also significantly less blood loss in the anterior group than on the posterior treatment group with mean EBL of 90 cc and 258 cc respectively ( p = .008). There were no wound complications in the anterior treatment group while there were four postoperative wound infections in the posterior treatment group requiring irrigation and débridement. Conclusions Reached: Anterior stabilization is a valid alternative to posterior stabilization in the treatment of facet dislocations and subluxation and may be preferred in the treatment of the polytrauma patient.